Patient satisfaction toward medical ward services in a Teaching Hospital (TH) and a General Hospital (GH) - Mohd Zamri Md Ali,; Than Winn,; Mohd Ayub Sadiq,; Mohd Ayub Sadiq,; Aziz Baba,; Rosemi Salleh, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
A contrived cross-sectional study was conducted among medical inpatients admitted to the medical wards of a Teaching Hospital (TH) and a General Hospital (GH) in the Kota Bharu district to study patient satisfaction toward medical ward services in both hospitals. A validated, self-administered patient satisfaction toward medical ward service (PSMWS) questionnaires were given to 376 eligible medical inpatients. This study showed that demographic characteristics of two groups were similar except median family income higher among TH group (RM925 vs. RM775, p<0.05), median PatientS Out-of-Pocket Expenditure (POE) was higher among TH group (RM3j vs. RM28, p<0.001), mean Length of Stay (LOS) was longer among TH respondents(j.8 vs. 3.3 days, p